30 Del. Laws 484 (1919) - (:unkn) unknown (My University, 1918)
Minors Under Fifteen Not to Use Gun Unless Accompanied by an Adult, § 2382 A. Sec. 25 A: Prohibited any minors under age fifteen from hunting game birds or game animals with a rifle or shotgun unless accompanied by an adult who is lawfully hunting.
Keywords: HUNTING REGULATION - MINORS